Shopaholic Lifestyle: A Phenomenological Study of Overseas Student in Yogyakarta - Rahmayanti, Siti; Abdullah, Sri Muliati (Research Horizon, 2025)
Yogyakarta, known as the “City of Students,” has seen a growing trend of shopaholic behavior among migrant students, driven by social, psychological, and economic factors. This study aims to explore the phenomenon of shopaholic lifestyle among migrant students in Yogyakarta by using qualitative approaches and phenomenological methods. The main focus of this study is to understand the triggers, subjective meanings, and emotional, social, and financial impacts of excessive consumptive behavior. Data was obtained through in-depth interviews with five migrant students aged 23–24 years old who had experience with impulsive shopping behavior. The results of the study revealed four main themes, namely: difficulties in financial management, momentary emotional satisfaction from shopping behavior, strong influence of the social environment and media, and negative impacts on financial and psychological conditions. College students tend to view shopping as an escape from stress, boredom, or academic pressure, with motivation influenced by digital promotion and consumerist culture. This study confirms that the shopaholic lifestyle is the result of a complex interaction between internal and external factors that reinforce irrational consumption patterns. These findings are expected to be the foundation for designing financial literacy strategies and psychosocial interventions for migrant students.